Interpretação conjunta de dados de GPR e medidas de permeabilidade sobre um análogo de reservatório siliciclástico falhado na Bacia de Tucano, no NE do Brasil - Miranda, Hugo César Brandão de (2004)
It is presented an integrated geophysical investigation of the spatial distribution of faults and deformation bands (DB´s) in a faulted siliciclastic reservoir analogue, located in Tucano Basin, Bahia State, northeastern Brazil. Ground Penetrating Radar (GPR) and permeability measurements allowed the analysis of the influence of DB´s in the rock permeability and porosity. GPR data were processed using a suitable flow parametrization in order to highlight discontinuities in sedimentary layers. The obtained images allowed the subsurface detection of DB´s presenting displacements greater that 10 cm. A good correlation was verified between DB´s detected by GPR and those observed in surface, the latter identified using conventional structural methods. After some adaptations in the minipermeameter in order to increase measurement precision, two approaches to measure permeabilities were tested: in situ and in collected cores. The former approach provided better results than the latter and consisted of scratching the outcrop surface, followed by direct measurements on outcrop rocks. The measured permeability profiles allowed to characterize the spatial transition from DB´s to undeformed rock; variation of up to three orders of magnitude were detected. The permeability profiles also presented quasi-periodic patterns, associated with textural and granulometric changes, possibly associated to depositional cycles. Integrated interpretation of the geological, geophysical and core data, provided the subsurface identification of an increase in the DB´s number associated with a sedimentary layer presenting granulometric decrease at depths greater than 8 m. An associated sharp decrease in permeability was also measured in cores from boreholes. The obtained results reveal that radagrams, besides providing high resolution images, allowing the detection of small structures (> 10 cm), also presented a correlation with the permeability data. In this way, GPR data may be used to build upscaling laws, bridging the gap between outcrop and seismic data sets, which may result in better models for faulted reservoirs